Variation in the helminth community structure in bank voles (Clethrionomys glareolus) from three comparable localities in the Mazury Lake District region of Poland - Behnke, J.M.; Barnard, C.J.; Bajer, A.; Bray, D.; Dinmore, J.; Frake, K.; Osmond, J.; Race, T.; Sinski, E. (Cambridge University Press, 2001)
We tested the null hypothesis that populations of hosts trapped in isolated neighbouring locations showing comparable habitat quality, should support similar helminth parasite communities. The study was undertaken in a 2-week period in late summer in NE Poland in a single year, thereby eliminating seasonal and between-year variation in parasite burdens. A total of 139 Clethrionomys glareolus (bank vole) were sampled from 3 forest sites of similar habitat quality. Total species richness was 11 (6 nematodes and 5 cestodes) with 85±6% of the voles carrying at least 1 species and an overall mean species richness of 1±4. At the component community level, the fewest species of helminths were recorded from site 2 (n=6, compared with 9 at each of the other sites), but site 3 had the lowest Berger-Parker Dominance Index and the highest Simpson's Index of Diversity. At the infracommunity level, site 3 had the highest mean no. of helminthspecies}vole, the highest mean Brillouin's Index of Diversity but the lowest mean no. of helminths/vole. Voles from sites 1 and 3 differed in the nematodes that were most common (site 1, Heligmosomum mixtum ± 95%; site 3, Heligmosomoides glareoli ± 79±3%). At site 2 no species exceeded 50% but prevalence of Syphacia petrusewiczi was higher than at the other sites. The prevalence of cestodes was too low to test reliably (12±9%), but the highest prevalence of adult cestodes was recorded at site 1 (22±5%compared with 4±9 and 1±7%for sites 2 and 3 respectively). Host sex did not ifluence infection, but mean species richness increased with age. The different sites were responsible for most of the variation in our data, and the intrinsic factors (sex and age) were less important in shaping the component community structure of helminths. We conclude that even locations in relative close proximity to one another (13±25 km), selected on the basis of similar habitat quality, have rodent populations that differ in their helminth parasite communities, although for reasons other than the factors quantified in the present study.